Software quality - complexity and challenges of software engineering in emerging technologies : 9th International Conference, SWQD 2017, Vienna, Austria, January 17-20, 2017, proceedings /: 9th International Conference, SWQD 2017, Vienna, Austria, January 17-20, 2017, proceedings. (2017) - Unknown
No abstract available